2010
DOI: 10.3109/07434618.2010.505609
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Communication Intervention for Speaking and Non-speaking Children with Intellectual Disabilities

Abstract: The current study demonstrates the effectiveness of an intervention that addresses both home care and day care for children with intellectual disabilities while also taking the large individual differences between the children into account. The KLINc Studio intervention was designed to improve the language development, communication skills, and emergent literacy of 10 children with complex communication needs. The focus of the anchor-based intervention program was on the stimulation of vocabulary learning via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…The results obtained corroborate literature findings regarding the gain in oral communication through phrasal structures containing adequately organized elements such as articles, nouns, verbs, pronouns, preposition, and conjunctions 20,22,29,31 . It can be argued that the repetition of phrasal structures with gradual and systematic introduction of slight modifications in syntactic elements, associated to the transparency and familiarity of the symbols, led to the implementation of auditory working memory, which has great influence on language issues presented by individuals with DS.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The results obtained corroborate literature findings regarding the gain in oral communication through phrasal structures containing adequately organized elements such as articles, nouns, verbs, pronouns, preposition, and conjunctions 20,22,29,31 . It can be argued that the repetition of phrasal structures with gradual and systematic introduction of slight modifications in syntactic elements, associated to the transparency and familiarity of the symbols, led to the implementation of auditory working memory, which has great influence on language issues presented by individuals with DS.…”
Section: Discussionsupporting
confidence: 81%
“…The type of study proposed found support in international literature regarding AAC. Although its importance is recognized, few references are found 22,29 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations